Dermoid of spermatic cord diagnostic dilemma - Ambre, Sagar Ramesh; Dnayanmote, Anuradha; Chakraborty, Mayank; Shirke, Omkar; Bhatnagar, Shubhi; Akhil, Shrrey (International Surgery Journal, 2017)
Dermoid cyst of spermatic cord is extremely rare pathology. We present the case of 25-year-old male who presented with a right groin lump, thought to be a hernia. The swelling was reducible and cough impulse was positive. There was a lump found close to the right groin apart from hernia. After dissection it was seen as protruding out superficial ring and was attached to the spermatic cord. The final histopathological analysis gave the diagnosis of a dermoid cyst.